Deteksi Kesehatan Keuangan Industri Department Store Selama Periode 2020 – 2022 Menggunakan Financial Discriminant Models Altman Z-Score - Irhamdani Irhamdani; Rival Perdana; Rizki Ramadhan; Yanuar Buana Paksi; Yudha Hartlanda Martianto; Yanuar Ramadhan6 (AKUNTANSI 45, 2024)
This study aims to determine the condition of the company's financial health during the 2020-2022 period. The sampling technique used is purposive sampling. This research was conducted on department store companies. The data used in this study is secondary data obtained from the websites of each company. This research tries to find the factors causing the decline in the company's liquidity level through the company's financial report data during the 2020-2022 period, based on the research conducted several factors were found to be the phenomenon of a decrease in the level of sales that occurred due to the impact of social restrictions large-scale so that it affects the company's sales level and disruption of the company's cash flow. From the results of the research conducted, the authors hypothesize several solutions that other similar companies can use in dealing with the impact of the crisis, some example is to create new market options that utilize technology such as increasing market networks and dividing the ratio of direct sales and indirect sales. Research results and theoretical implications obtained by the authors are expected to be used for the next 2-3 years after the crisis ends.